Immune landscape of renal cell carcinoma with metastasis to the pancreas - Kippenberger, Maximilian; Schoenberg, Gita; Kaczorowski, Adam; Schneider, Felix; Böning, Sarah; Sun, Angela; Schwab, Constantin; Görtz, Magdalena; Schütz, Viktoria; Stenzinger, Albrecht; Hohenfellner, Markus; Duensing, Anette; et al. (Urologic oncology, 2024)
Introduction - Clear cell Renal Cell Carcinoma (ccRCC) has a poor prognosis once metastatic. However, certain metastatic sites have been reported to have a different impact on the patient prognosis. For example, patients with pancreatic metastases have a much more favorable prognosis than those with metastases to other organs. The biological basis for this observation remains poorly understood. The aim of this study was to characterize the immune landscape of pancreatic metastases and the corresponding primary tumors in order to identify possible immunological features that correlate with disease biology. - Patients and Methods - A detailed assessment of immune cell populations was performed using a total of 1,700 microscopic images from ccRCCs from 11 patients, their corresponding pancreatic metastases and ccRCCs from 10 patients without pancreatic metastases. Tumor specimens were stained for CD45, CD8, CD163 and FOXP3 and the densities of the respective immune cells were assessed semiquantitatively in the intratumoral and extratumoral compartment. Multispectral imaging was performed in selected tumors. - Results - We found that pancreatic metastases show the lowest intratumoral infiltration with CD8+ cytotoxic T lymphocytes of all tumor specimens analyzed. The frequency of CD8+ lymphocytes was on 1.9 fold lower in pancreatic metastases (median density 8.3 cells per field of view [FOV]=1.23 mm2) when compared to the corresponding primary tumor (15.6 cells per FOV, P=0.0002) and more than 3-fold lower when compared to ccRCCs without pancreatic metastases (27.2 cells per FOV, P=0.0012). There was also a significantly reduced intratumoral infiltration with immunosuppressive FOXP3+ lymphocytes in pancreatic metastases (2.6 cells per FOV, P=0.009) and corresponding primary tumors (2 cells per FOV, P=0.028) when compared to ccRCCs without pancreatic metastases (5.6 cells per FOV). - Conclusions - In this proof-of-concept study, we show that pancreatic metastases of ccRCC present with unique immunological features including a low intratumoral density of CD8+ and FOXP3+ lymphocytes. The low counts of CD8+ and FOXP3+ lymphocytes may reflect less aggressive features of ccRCC with pancreatic metastasis that may result in a more favorable patient prognosis.